Cross-Shelf Exchange in the Southwestern Atlantic Shelf: Climatology and Extreme Events - Berden, Giuliana; Piola, Alberto R.; Palma, Elbio D. (Frontiers in Marine Science, 2022)
The variability and drivers of the cross-shore exchanges between the Southwestern Atlantic shelf and the open ocean from 30 to 40°S are analyzed using a high-resolution ocean model reanalysis at daily resolution. The model’s performance was first evaluated using altimetry data, and independent mooring and hydrographic data collected in the study area. Model transports are in overall good agreement with all other estimates. The record-mean (1993-2018) cross- shore transport is 2.09±1.60 Sv. 73% of the shelf-open ocean exchange occurs in the vicinity of Brazil-Malvinas Confluence (∼38°S) and 20% near 32°S. This outflow is mostly contributed by northward along-shore transport through 40°S (63%) and the remaining by southward transport through 30°S (37%). The cross-shore flow presents weak seasonal variations, with a maximum in austral summer, and high variability at subannual and weekly time scales. The latter is mainly associated with abrupt wind changes generated by synoptic atmospheric systems. Along-shore wind variations set up sea-level changes in the inner shelf which in turn drive large anomalies in the associated geostrophic along-shelf flow. Episodes of extreme offshore transport that reach up to 9.45 Sv and last about 2 days are driven by convergence of these along-shore flows over the shelf. Large exports of shelf waters lead to freshening of upper open ocean waters as revealed by in-situ and satellite observations. In contrast, onshore extreme events drive open ocean water intrusions of up to 6.53 Sv and last less than 4 days. These inflows, particularly the subtropical waters from the Brazil Current, induce a substantial salinification of the outer shelf.